El estrés y su influencia en el desempeño laboral de los colaboradores de Consermet SAC - Trujillo - 2016 - Luján Quezada, Luz Virginia (2017)
The research was carried out with the objective of determining the influence of stress on the work performance of the employees of the Consermet SAC Company, in the city of Trujillo. In this research report we used the descriptive design Transectional and the methodology used for data collection was the survey as a technique and the questionnaire as an instrument, which consisted of 30 questions. The study population consisted of 50 collaborators, so census sampling was used. Based on the results of this study, the hypothesis was accepted for the above problem, which states that stress significantly influences the work performance of the employees of Consermet SAC, which was tested and tested by the test t-Student statistics. According to the results obtained, it was concluded that the employees of this company, have high levels of stress, originated mainly by the demands of tasks and role, significantly reducing their level of work performance.